2018
DOI: 10.15666/aeer/1605_53115322
|View full text |Cite
|
Sign up to set email alerts
|

Phytosociology of We Ed Communit Y in Culture of Cowpea ( Vigna Unguiculata L. Walp ) and Controlling Possibilities With P Re - Emergent Herbicides

Abstract: This study has aimed to diagnose and compare the predominant weed species in cowpea crop in the Amazon region and to evaluate the effectiveness of herbicides applied in pre-emergence. The weed sampling was obtained before planting, the cowpea cultivar was BRS Aracê, by collecting all the plants present within a 0.25 m² hollow frame, randomly thrown 40 times in experimental area to calculate the phytosociological indices. The herbicide efficiency experiment was conducted in a randomized block design with four r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…The results for grain yield showed that all treatments were satisfactory when compared to the coexistence of the crop with the weeds that significantly reduced productivity. Similar results were obtained by Gonzaga et al (2018), who observed a 67% reduction productivity in cowpea yield with weeds present. According to Lamego et al (2011), the low yield in some treatments can be explained by the phytotoxicity exhibited by the crop, which reduces growth and causes the death of some plants, affecting productivity.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The results for grain yield showed that all treatments were satisfactory when compared to the coexistence of the crop with the weeds that significantly reduced productivity. Similar results were obtained by Gonzaga et al (2018), who observed a 67% reduction productivity in cowpea yield with weeds present. According to Lamego et al (2011), the low yield in some treatments can be explained by the phytotoxicity exhibited by the crop, which reduces growth and causes the death of some plants, affecting productivity.…”
Section: Resultssupporting
confidence: 89%
“…One of the main problems faced by producers in the northern parts of Brazil is weed interference (Costa et al, 2017). Since sowing is carried out using wider spacing, crops show slow initial growth, allowing weeds to compete directly with cowpea for space, water, light and nutrients (Lamego et al, 2011;Linhares et al, 2014), and consequently, reduce the crop yield by more than 66% (Gonzaga et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in grain yield due to weed interference throughout the cowpea cycle is quite variable in several studies, with values of 64% (Yadav et al, 2018), 66% (Gonzaga et al, 2018), 68% (Adigun et al, 2014) and up to 90% (Freitas et al, 2009). For phaseolus species, this same trend in reducing yield happens (Frenda et al, 2013;Esmaeilzadeh & Aminpanah, 2015;Odero & Wright, 2018).…”
Section: /6mentioning
confidence: 99%
“…Alguns trabalhos de pesquisa realizados em área de savana do estado de Roraima com o intuito de levantar o banco florístico da mesma, no entanto, os trabalhos realizados para levantamento dos parâmetros fitossociológicos se restringem às áreas já cultivadas (CRUZ et al, 2009;ALBUQUERQUE et al, 2013;ALBUQUERQUE et al, 2014;EVANGELISTA et al, 2015;ALBUQUERQUE et al, 2017a;ALBUQUERQUE et al, 2017b;GONZAGA et al, 2018;CRUZ et al, 2018). Porém existem poucos trabalhos que contemplam o levantamento fitossociológico das espécies vegetais da savana de Roraima ainda não incorporada ao sistema produtivo (MIRANDA; ABSY, 1997; MIRANDA; ABSY, 2000; FLORES; RODRIGUES, 2010).…”
Section: Introductionunclassified